(3EVGAI GdQGehS hEVGaI GdfGehS Ydi EVGAI GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3aUd GdMGA GdeYLeI (B: (3bhdg GdNHQ eMQcI (B: (3GdfHC bdJ hbO SHb GdaQb HjfgeG , hCf GdfHC eajO Hchfg Yf CeQ YXje ceG bjO GdQGZH hZjQg ef CFeI GdGTJbGb s
(3BNQgG (B:s
(3hJQLefG eG MQQfGg HEVGAI GdQGehS hEVGaI GdfGehS Ydi EVGAI GdbGehS hBNQ OYhGfG Cf GdMeO ddg cedJ MGTjI GdbGehS GdeHGQcI s
(3GdLRA GdQGHY ef GdfSNI GdSGHbI faSgGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs